DPA - Dimensional Personality Assessment - 1 Laura Rapanà, 2 Claudio Barbaranelli (Marp Edizioni, 2019)
The present paper examines the theoretical bases, the psychometric properties and the applicative uses of the Dimensional Personality Assessment, a process evaluation tool of personality inspired by criterion A for the personality disorder described in the alternative model introduced in the latest version of the Diagnostic and Statistical Manual of Mental Disorder. the Dimensional Personality Assessment is a questionnaire that allows the self-evaluation of the person's functioning with regard to the following four dimensions and their respective three sub-dimensions: identity (Self-esteem, Emotional Experience, Sense of Self), Self-direction (Self-reflective Ability, Pursuit of Goals, Standards and inner Values), Empathy (Understanding the Effects of one's own behavior on others, comprehension and Appreciation of the Experience, tolerance of others' Point of View) and intimacy (behavior of Mutual respect, Desire and capacity of closeness, Depth and Duration of the relationship). the questionnaire is completed by a control scale for the measurement of Social Desirability (lie Scale). the Dimensional Personality Assessment consists of a total of 92 items measured on a 5-points likert Scale. the Dimensional Personality Assessment has undergone a rigorous examination of its psychometric characteristics, such as its factor structure, its reliability, and the correlation with scales from several instruments used in clinical practice and in applied research (such as the big Five Questionnaire-2 and the Symptom checklist-90 revised, among others). the Dimensional Personality Assessment was validated on a sample of over 500 non-clinical adults, and on a group of over 200 patients on psychotherapeutic treatment. the present paper describes the Dimensional Personality Assessment research project and its use during a psychotherapeutic treatment as an evidence-based instrument for the results.